Late right ventricular performance after mitral valve repair assessed by exercise echocardiography - Ragnarsson, Sigurdur (Gen Thorac Cardiovasc Surg, 2018)
OBJECTIVES: The aim of the study was to evaluate the right ventricular (RV) performance during exercise in patients who underwent mitral valve repair for chronic mitral valve insufficiency relative to healthy individuals and to assess exercise capacity using a semisupine ergometer. METHODS: We studied 56 patients who underwent mitral valve repair for degenerative posterior mitral leaflet prolapse between 2005 and 2014 and a control group of 13 healthy individuals. Clinical data were collected prospectively, and echocardiographic measurements of RV function were obtained at rest and at peak exercise. RESULTS: One-third of the study patients had RV systolic dysfunction as indicated by tricuspid annular plane excursion (TAPSE) at rest. Resting TAPSE was lower in the study group (16.7 ± 3.3 mm) than in the control group (24.4 ± 4.3 mm), p < 0.001. TAPSE increased in both groups during exercise and exercise was shown to have a significant main effect on TAPSE F(1, 52) = 80, p < 0.001. TAPSE increased more in the control group and an interaction was detected between the participant groups (study group vs. control group) and exercise, F(1, 52) = 24, p < 0.001. In the study group, Poor postoperative RV function was associated with preoperative left ventricular dilatation but was not correlated with impaired maximum exercise capacity. CONCLUSIONS: Despite the excellent clinical outcome during rest and exercise after mitral valve repair, our results suggest patients that have undergone mitral valve repair due to posterior leaflet prolapse have significantly reduced RV function at rest and during exercise compared to healthy controls at long-term follow-up, as measured by TAPSE.